The use of Microsoft teams breakout rooms to encourage collaborative learning in synchronous online classroom - Nabila, Abdul Malek (UPM, 2022)
Maintaining student engagement and providing chances for collaborative learning are two issues that online courses can pose for both students and instructors. Utilising breakout rooms, distinct virtual spaces where small groups of students can collaborate, is one method to overcome these difficulties. Breakout rooms are one of the features available in Teams meetings. It is used to separate participants of a meeting into subgroup meetings. As noted, open dialogue and a fruitful exchange of views can sometimes be challenging in the main meeting room. As such, the use of breakout rooms enables students to gather in small groups for active discussion and brainstorming sessions during synchronous online classes.